KONSEKUENSI PEMBATALAN UNDANG-UNDANG RATIFIKASI TERHADAP KETERIKATAN PEMERINTAH INDONESIA PADA PERJANJIAN INTERNASIONAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to analyse the legal consequences of the repeal of a ratification act by the Constitutional Court in relation with the Indonesian Government s participation in the ratified or acceded international treaty. This normative legal research employs a collaborative method in data collecting process, viz. literature research to collect secondary data andfield research to equip and support the data collected from literature research. The data is analysed using a qualitative descriptive method Wefind that there is no correlation between the repeal of a ratification act and the participation of Indonesia in the international forum initiated by the repealed act.